Theoretical analysis and experimental study on physical explosion of stratospheric airship envelope - Song, Lin; Yang, Yanchu; Zheng, Zhidong; He, Zeqing; Zhang, Xiaojun; Gao, Heng; Guo, Xiqing (Frontiers in Materials, 2023)
The release of shock wave from a pressurized stratospheric airship explosion can produce serious damages to the environment. Shock wave overpressure can measure the degree of damage that an explosion can cause to buildings, the human body, etc. For obtaining the overpressure from an airship envelope explosion, explosion energy needs to be conducted firstly. Explosion energy is derived based on Brode’s Equation, Brown’s Equation and Crowl’s Equation, respectively. Afterwards, an equivalent TNT computational model is applied to calculated overpressure with the explosion energy. In order to verify the accuracy of the computational model, a ground test is conducted. The experimental result shows that the computational model based on Crowl’s Equation is more accurate than other two equations. Finally, the effect of geometric scale ratio, pressure difference, and the sort of gas on the explosion overpressure was discussed. This paper can provide a relatively effective calculation method on shock wave overpressure for airships envelope explosion.